Graphene and related materials in hierarchical fiber composites: Production techniques and key industrial benefits. - Valorosi, F.; De Meo, E.; Blanco-Varela, T.; Martorana, B.; Veca, A.; Pugno, N.; Gomez, J.
Fiber-reinforced composites (FRC)are nowadays one of the most widely used class of high-tech materials. In particular, sporting goods, cars and the wings and fuselages of airplanes are made of carbon fiber reinforced composites (CFRC). CFRC are mature commercial products, but are still challenging materials. Their mechanical and electrical properties are very good along the fiber axis, but can be very poor perpendicular to it; interfacial interactions have to be tailored for specific applications to avoid crack propagation- and delamination; fiber production includes high-temperature treatments of adverse environmental impact, leading to high costs. Recent research work shows that the performance of CFRC can be improved by addition of graphene or related 2-dimensional materials (GRM). Graphene is a promising additive for CFRC because: 1)Its all-carbon aromatic structure is similar to the one of carbon fiber (CF). 2)Its 2-dimensional shape, high aspect ratio, high flexibility and mechanical strength allow it to be used as a coating on the surface of fiber, or as a mechanical/electrical connection between different fiber layers. 3)Its tunable surface chemistry allows its interaction to be enhanced with either the fiber or the polymer matrix used in the composite and 4)in contrast to carbon fibers or nanotubes, it is easily produced on a large scale at room temperature, without metal catalysts. Here, we summarize the key strategic advantages that could be obtained in this way, and some of the recent results that have been obtained in this field within the Graphene Flagship project and worldwide.
Keywords: CARBON NANOTUBES; GRAPHENE